Pengaruh manajemen risiko terhadap keberlanjutan bisnis pada UMKM - Aqil, Bima Labibul (Maliki Interdisciplinary Journal, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy, particularly in generating employment opportunities and promoting income distribution. However, in facing dynamic and uncertain business environments, MSMEs are exposed to various risks that may threaten their business sustainability. This study aims to analyze the influence of risk management on MSME business sustainability. The method used is a literature review by examining various scholarly sources related to risk management and business sustainability. The findings indicate that systematic risk management implementation enables MSMEs to identify, analyze, and mitigate potential risks, both internal and external. Furthermore, risk management contributes to improving operational efficiency, strengthening stakeholder trust, and enhancing business resilience in times of crisis. Business sustainability is not solely determined by short-term profits but also by the ability of enterprises to adapt and survive in the long term. Therefore, consistent and integrated risk management practices are essential factors in maintaining stability and ensuring the growth of MSMEs amid increasingly complex global competition.